2015
DOI: 10.1016/j.tsf.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic phase transitions in a ferromagnetic thin film system: A Monte Carlo simulation study

Abstract: Dynamic phase transition properties of ferromagnetic thin film system under the influence both bias and time dependent magnetic fields have been elucidated by means of kinetic Monte Carlo simulation with local spin update Metropolis algorithm. The obtained results after a detailed analysis suggest that bias field is the conjugate field to dynamic order parameter, and it also appears to define a phase line between two antiparallel dynamic ordered states depending on the considered system parameters. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Remarkably, it is necessary to underline that the function relation between T C and h 0 is approximately linear, which is because the magnetic energy derived from Zeeman energy governs the energy produced by the spin interaction with the increase of h 0 . Similar results have been found in previous studies [38,41,42]. In figure 8(e), T C increases with the increase of ω, while it is no longer sensitive to the change of ω when ω>0.02π.…”
Section: Phase Diagramsupporting
confidence: 91%
See 1 more Smart Citation
“…Remarkably, it is necessary to underline that the function relation between T C and h 0 is approximately linear, which is because the magnetic energy derived from Zeeman energy governs the energy produced by the spin interaction with the increase of h 0 . Similar results have been found in previous studies [38,41,42]. In figure 8(e), T C increases with the increase of ω, while it is no longer sensitive to the change of ω when ω>0.02π.…”
Section: Phase Diagramsupporting
confidence: 91%
“…There exist P-type, N-type and Q-type magnetic behaviors in the system under certain parametric conditions [39]. They also studied the dynamic magnetic properties of mixed-spin (1/2, 3/2) Ising ferrimagnetic system [40] and ferromagnetic thin film system [41] under an oscillating external magnetic field. Based on MC simulation, DPT in La 2/3 Ca 1/3 MnO 3 magnets was studied by Alzate-Cardona et al and typical conclusion was illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the critical exponents of the two dimensional kinetic Ising model subjected to a square-wave oscillatory magnetic field are consistent with the universality class of the corresponding equilibrium Ising model [5]. Moreover, it is recommended in these references [12,15,17,19] that bias field appears to be a conjugate field of the dynamic order parameter, which is time averaged magnetization over a full cycle of the external field. In addition to the consensus in dynamic phase transitions and equilibrium phase transitions, however, there are inconsistencies in the literature, in view of the universality class of the spin systems.…”
Section: Introductionmentioning
confidence: 98%
“…From their analysis, the authors concluded that amplitude and period of the oscillatory magnetic field play an important role on the dynamic characters of the considered magnetic system. Since then, many theoretical [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and several experimental works [16][17][18][19][20] have been carried to understand the origin of the dynamic phase transitions. Based on the some of the previously published studies, it is possible to say that there is a good consensus between dynamic phase transitions and equilibrium phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…This is because when a material is exposed to a dynamically-applied magnetic field (both biased and time-varying oscillatory fields), the system does not simultaneously respond to both fields, but the order of the magnetic moment depends on the oscillating field over time, leading to dynamic phase transitions [36,37]. Vatansever and Polat [38] researched materials, including triangular lattice and ferromagnetic thin film systems, under biased and oscillating magnetic fields and found that the amplitude of the oscillating magnetic fields affected the dynamic critical properties of the system [39]. Ertaš et al observed the dynamic hysteresis line behaviors of Ising ferromagnetic systems and discussed the effect of temperature on exchange coupling and the dynamic hysteresis behaviors [40][41][42].…”
Section: Introductionmentioning
confidence: 99%